Poly Implant Prothèse silicone breast implants: implant dynamics and capsular contracture - Bachour, Y. (Eur J Plast Surg, 2018)
BACKGROUND: The Poly Implant Prothèse (PIP) implants were withdrawn from the market in 2010 due to the use of low-grade silicone, causing a high risk for implant rupture. The aim of this study was to investigate the implant dynamics of PIP breast implants, as well as to determine the rate and predictors of implant gel bleeding, rupture, and capsular contracture in PIP implants. METHODS: Eighty women with a total of 152 PIP implants who underwent a reoperation in 2012 were enrolled in this study. Physical investigation included assessing the Baker score and demographics were retrospectively traced in medical records. The pre- and post-operative volumes of the implants were calculated and their state was determined intraoperatively by the surgeon. RESULTS: The implants were removed after a mean implant duration of 11 ± 2.1 years. Gel bleed and implant rupture occurred in respectively 42 and 25% of the implants. Intact implants had post-operative volume increase as well as decrease. There was a correlation between gel bleeding and more post-operative implant volume increase (P ≤ 0.05). Capsular contracture had a protective effect against post-operative implant volume increase (P ≤ 0.05), while a post-operative implant volume increase provided a protective influence in developing capsular contracture (P ≤ 0.05). Additionally, implant rupture led to a higher risk of capsular contracture (P ≤ 0.05). CONCLUSIONS: We managed to illustrate that PIP implant shells were too permeable and that there is a correlation between gel bleeding and the increase of the post-operative implant volume. Implant rupture led to a higher risk for developing capsular contracture. Level of evidence: Level III, risk / prognostic study. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00238-018-1427-y) contains supplementary material, which is available to authorized users.